Non-canonical functions of EZH2 in cancer - Zimmerman, Sarah M.; Lin, Phyo Nay; Souroullas, George P. (Frontiers in Oncology, 2023)
Mutations in chromatin modifying genes frequently occur in many kinds of cancer. Most mechanistic studies focus on their canonical functions, while therapeutic approaches target their enzymatic activity. Recent studies, however, demonstrate that non-canonical functions of chromatin modifiers may be equally important and therapeutically actionable in different types of cancer. One epigenetic regulator that demonstrates such a dual role in cancer is the histone methyltransferase EZH2. EZH2 is a core component of the polycomb repressive complex 2 (PRC2), which plays a crucial role in cell identity, differentiation, proliferation, stemness and plasticity. While much of the regulatory functions and oncogenic activity of EZH2 have been attributed to its canonical, enzymatic activity of methylating lysine 27 on histone 3 (H3K27me3), a repressive chromatin mark, recent studies suggest that non-canonical functions that are independent of H3K27me3 also contribute towards the oncogenic activity of EZH2. Contrary to PRC2's canonical repressive activity, mediated by H3K27me3, outside of the complex EZH2 can directly interact with transcription factors and oncogenes to activate gene expression. A more focused investigation into these non-canonical interactions of EZH2 and other epigenetic/chromatin regulators may uncover new and more effective therapeutic strategies. Here, we summarize major findings on the non-canonical functions of EZH2 and how they are related to different aspects of carcinogenesis.